To develop biodegradable Mg-based metal ceramic composites as bone implant material - Rai P.; Chaturvedi R.K.; Mishra A.; Kumar V.; Singh V.K. (My University, 2025)
Biodegradable materials for orthopaedic implants have gained much attention due to their similar properties to natural bone. Magnesium-based alloys are considered the best biodegradable material for bone substitute materials. However, magnesium alloys have very high corrosion rate. Research has been focused to fabricate and to make their composites to control their corrosion rates in human physiological environment and to develop the ability of forming bone-like apatite layer on their surface. In the present study, Mg–Zn–Mn metal alloys were selected for making their composites with hydroxyapatite (HAp) and bio-glasses. HAp was prepared by the co-precipitation method and bio-glasses (45S5P7) were prepared by the melting and quenching method. Samples from metal–ceramic composites were prepared by the powder metallurgy route in various compositions. Furthermore, samples were characterized for their phases, microstructure, corrosion behaviour, mechanical properties and bioactivity. The composites showed bioactivity in simulated body fluid (SBF) solution and their young’s modulus values were obtained near to the human bone. The degradation properties, as studied in SBF solution, revealed Mg-based alloy composites having approximately 10% bio-active glasses and 10% β-tri-calcium phosphate resulted in the reduction of the corrosion rate. © 2020, Indian Academy of Sciences.